2017
DOI: 10.1002/ejhf.1101
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic diversity of high‐density lipoprotein explains its association with clinical outcome in patients with heart failure

Abstract: This study shows marked differences in composition of the HDL proteome between HF survivors and deaths. The strongest differences were seen in proteins reflecting crosslinking of actin filaments and alveolar capillary membrane function, posing potential pathophysiological mechanisms underlying the association between HDL and clinical outcome in HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 27 publications
(42 reference statements)
4
32
0
Order By: Relevance
“…Interestingly, in a previous smaller study, we also found PSPB as the most significantly enriched protein of HDL CHD (31). Longitudinal studies found PSPB-enriched HDL as a significant predictor of mortality in T2DM patients undergoing hemodialysis, as well as in patients with heart failure (32,33). We also found HDL T2DM+CHD and HDL T2DM relatively deprived of apoE and apoD, respectively (Figure 2), which were also inversely associated with prevalent or incident diabetes by others (34).…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, in a previous smaller study, we also found PSPB as the most significantly enriched protein of HDL CHD (31). Longitudinal studies found PSPB-enriched HDL as a significant predictor of mortality in T2DM patients undergoing hemodialysis, as well as in patients with heart failure (32,33). We also found HDL T2DM+CHD and HDL T2DM relatively deprived of apoE and apoD, respectively (Figure 2), which were also inversely associated with prevalent or incident diabetes by others (34).…”
Section: Discussionsupporting
confidence: 67%
“…In a recent proteomic study published by our group, 49 differently expressed proteins were identified between deaths ( n = 45) and survivors ( n = 45) in patients with HF. However, Emmens et al . focused on a depth investigation of the multifunctional HDL proteome to reveal underlying pathophysiological mechanisms that could explain the association between HDL and clinical outcome, while this study covered the whole plasma proteome in patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 100 patients with HF in this study were selected from the EU FP7 funded BIOSTAT‐CHF (A systems BIOlogy Study to TAilored Treatment in Chronic Heart Failure) project. This was a multicentre clinical study in Europe that aimed to identify poor outcomes in HF patients with standard treatment using a systems biology approach (including demographics, biomarkers, genetics, and proteomics) . This project was conducted according to the Declaration of Helsinki that was approved by national and local ethics committees.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations